A new proof of a contrast function for bounded component analysis and further analysis. (September 2018) - Gao, Wei; Fan, Shen; Togneri, Roberto; Sreeram, Victor
Abstract: Bounded Component Analysis (BCA) solves the Blind Source Separation (BSS) problem based on geometric assumptions. This paper introduces a new proof of a BCA contrast function, derived from elementary matrices, Gauss–Jordan elimination and convex geometry. The new proof and further analysis provide additional insight into a key assumption of BCA. In addition, an interpretation is presented to clarify one of the limitations of the instantaneous BCA algorithm. Experiments on audio sources support our analysis.